Taxonomic Study for the New Record Orobanche armena Tzvelev (Orobanchaceae) in Iraq - Abdullah Shakur Sardar (Zanco Journal of Pure and Applied Sciences, 2019)
Orobanche armena Tzvelev is a new plant record within Orobanchaceae family in Iraq, from Qandil mountain (North-East of Erbil) within Rowanduz district (MRO). Identification and morphological study have been done, these illustrated by graphs. Pollens characters have been clarified like shapes, colors, sizes, surface ornamentation and numbers. In addition, some features of the leaf and stem anatomy have been examined